Peningkatan Kemampuan Berbahasa Indonesia dalam Membentuk Karakter Mahasiswa Era Revolusi Industri 5.0 - Dewirahmadanirwati Dewirahmadanirwati (Fakultas Sastra Universitas Ekasakti, 2021)
The improvement of language skills in the higher education environment is expected to be able to help students get to know themselves, their culture, and the culture of others, so that they can form polite and polite language characters. The era of the industrial revolution 5.0 which first appeared in Japan in 2015, brought a new civilization in the educational environment, which made humans the center of innovation by deepening the integration of technology in improving the quality of life, sustainable social responsibility. The vision of society 5.0 demands a transformation in learning, especially in terms of the needs of students, the preparation and organization of teaching materials, and the pattern of mix in learning. This study describes the improvement of Indonesian language skills in shaping the character of students in the Industrial Revolution era 5.0, which is viewed from the needs of students. Lecturers as agents of change in forming smart, skilled, innovative and creative young people need to make changes in preparing lecture materials based on current technological developments.